ANALISIS KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH MENGEMBANGKAN SEKOLAH UNGGUL DI MASA PANDEMI - Yantoro; Muhammad Sholeh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the pandemic conditions that bring a huge impact on all sectors of life, especially in the educational context. Hence, certain steps are needed to implement education that can run well during this pandemic towards the managerial leadership of school principals who are reliable and able to develop superior schools during the pandemic. The purpose of the research was to analyze and describe the principal managerial leadership in developing superior schools during the pandemic at Mitra School Jambi University in realizing superior schools. The research was conducted at SDN 47/IV Jambi. The research used a qualitative approach with qualitative descriptive research. The results of the research and discussion can be concluded that the principal managerial leadership in developing superior schools during the pandemic begins with the stages of planning, implementation, and evaluation. Factors that influence the leadership of school principals in developing superior schools in the pandemic era are the principal's capability to build communication and collaboration with related parties, the ability of principals and teachers as academics in developing superior schools, qualified facilities and infrastructure, development of learning quality, and community participation (students’ parents or guardians, school committees, and private schools) in supporting the development of superior schools in the pandemic era.